TRANSDISCIPLINARY PERSPECTIVES OF EXPERIMENTAL PROJECTS OF SCIENCE ART - Shashkova, Liudmila (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Situations of interdisciplinarity in science in the last third of the 20th century are associated with going beyond disciplinary lines and the boundaries of laboratories. At the beginning of the 21st century, transdisciplinarity began to be considered as a bridge between the growth of scientific knowledge and the solution of specific problems in the practical sphere. The boundaries between scientific disciplines are becoming flexible and researchers are faced with questions of combining truth and practical utility. The aim and task of the research are to reveal the post-nonclassical perspective of the transdisciplinarity strategy of science. Research methodology. The methodological basis of the research is an interdisciplinarity approach and a transdisciplinary strategy of the philosophy of science, within which modern practices of science and art are analyzed as a form of cultural hybridization. Research results. Focusing on the analysis of current practices of science and art from the standpoint of the philosophy of science, the study represents a turn to a transdisciplinary strategy of updating the communicative and methodological experience of science. Communicative attempts to overcome disciplinary differences show the difficulties of solving the problem of combining truth and practical utility. The concept of a "tradingzone" is used to explain the possibilities of overcoming inconsistencies and establishing communication. Discussion. A special feature of Science Art is a new understanding of art and science associated with difficulties in the modern distinction between scientific research and an artistic project. The term "scientific art"indicates the original actual aesthetics and artistic practices and their inclusion as elements in the scientific process. Science Art is considered a transdisciplinary platform for the implementation of experimental projects arising from the consideration of complex phenomena in the process of becoming at the limits of the competencies of natural-social-humanitarian knowledge. Conclusions. Transdisciplinarity is considered a meta-level, which is based on a combination of various cognitive strategies and ways of thinking, a combination of theory and practice. The relevance of the methodology is strengthened by the tendency of coherence of socio-humanitarian and natural-scientific strategies. Science Art as a phenomenon of contemporary synthesis is such a new field of research at the intersection of science and art, where innovations arise.